2009
DOI: 10.1007/s10157-009-0254-7
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced macroautophagy occurs prior to apoptosis in proximal tubules in vivo

Abstract: Background. Autophagy is an intracellular bulk degradation process induced by cell starvation. Autophagy was recently reported to be induced by various stresses such as hypoxia, ischemia/reperfusion, toxins, and denatured proteins, and to affect cell survival and death. Light chain 3-II (LC3-II) is specifically located on double membrane-bound autophagosomes that envelop disused proteins or organelles. Method. Transgenic mice in which green fluorescent protein (GFP) was fused to LC3(LC3-GFP) were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 28 publications
3
84
1
1
Order By: Relevance
“…We showed that apoptosis of NRK-52E cells incubated under hypoxic conditions was significantly reduced by overexpression of sestrin-2 by caspase-3 activity and TUNEL assay. Our recent report (20) demonstrated that autophagy occurs before apoptosis in renal tubular cells during AKI. However, the role played by autophagy under apoptotic conditions remains controversial.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We showed that apoptosis of NRK-52E cells incubated under hypoxic conditions was significantly reduced by overexpression of sestrin-2 by caspase-3 activity and TUNEL assay. Our recent report (20) demonstrated that autophagy occurs before apoptosis in renal tubular cells during AKI. However, the role played by autophagy under apoptotic conditions remains controversial.…”
Section: Discussionmentioning
confidence: 90%
“…This is the first study to demonstrate that autophagy and mitophagy are induced, at least partially, by two signaling pathways in renal tubular cells after oxidative stress. We (20) previously using GFP-LC3 transgenic mice to investigate autophagy in kidney tissues during cisplatin nephrotoxicity and demonstrated that autophagy mainly occurred in the proximal tubules. Despite some controversies, most pharmacological, genetic, and knockout studies have supported a renoprotective role for autophagy in renal tubular cells in AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] These studies mainly used autophagy inhibitors (e.g., 3-methyladenine) or gene knockdown to modulate the activity of autophagy. Autophagy inhibitors are known to inhibit not only autophagy but also inhibit many other degradative pathways (e.g., proteasome, lysosomal function, mitochondrial function, or endocytosis).…”
Section: Discussionmentioning
confidence: 99%
“…The study of autophagy has revealed that autophagy deficiencies under nutrient excess conditions were involved in the pathogenesis of aging-related or metabolic diseases, including kidney disease (85,86). Currently, nephrologists are also entering this exciting field, and it has been revealed that autophagy has a renoprotective effect in a number of animal models including those used for acute kidney injury and aging (86)(87)(88)(89)(90)(91). More specifically, autophagy enhances cell adaptation to hypoxia and maintains podocyte homeostasis in aging mice (86,87).…”
Section: Sirt1 Induces Autophagy By Targeting Autophagy-related Genesmentioning
confidence: 99%